Model of Collaborative Learning to Improve Student’s Learning Ability in Nonformal Education Departement - Tristanti, Tristanti; Suharta, RB (Universitas Negeri Semarang, 2018)
The implementation of collaborative learning model in Nonformal Education is based on the condition of learning in classroom that not optimal. It can be seen from the activities of students are passive. The purpose of this model is to improve student’s ability in course of Life Skills Education Nonformal Education Department. The improving of student’s learning ability can be indicate by; (a) the improving of student motivation in contend, (b) the reducing of fear and shame of students in ideas, (c) the improving of interaction in communication among students. This study used Lesson Study method that includes three cycles. Each cycle is consisting of planning, implementation and evaluation or plan-do-see. The implementation of this study is focusing in the first cycle on the planning. The second cycle is based on the result from the cycle one. The last cycle is result of the evaluation from the cycle two. Data are analyzed by qualitative model to explain comprehensive result. The result of this study shows that the students have done three positive activities in the classroom. Firstly, the students are active in convey the ideas. This situation can be seen from the activities of students that appreciate each other’s. Secondly, the students areestablished positive interaction among students. The students are not shame in communication each other and the students have high confidence in communication. Lastly, students in the group discussion can evaluation each other and make conclusion from the result of discussion. The success of learning of life skills education is supported on various things; a) the participation active of student that trigger other students to communicate, b) the provision of equal opportunities for every student to argue so that no individual differences, c) feedback from educators to the students so that the students gain meaningful experience.